SEUDATI: KESENIAN TRADISIONAL ACEH SEBAGAI MEDIA DAKWAH DAN PELESTARIAN NILAI-NILAI ISLAM - Imam Juani; Jasmadi (AT-TAWASUL, 2024)
Seudati is a traditional Acehnese art that has historical roots in the culture and religion of the coastal communities of Aceh. This art was originally a religious ritual in the form of dhikr or meurateeb, which then developed into a performing art full of Islamic values. However, previous scientific studies tend to focus on the aesthetic and entertainment aspects of Seudati, so that they do not delve deeply into the historical dimensions and its role as a medium for preaching. This study aims to fill this gap by examining Seudati from a cultural and religious perspective, using a historical approach to trace its journey, function, and relevance in the modern era. The research method used is a qualitative approach, involving literature studies, in-depth interviews with Seudati practitioners, and direct observation of performances in several regions of Aceh. Data analysis was carried out using a descriptive analytical method to explore the relationship between local culture, religious values, and the shifting function of Seudati in modern society. The results of the study show that Seudati has a strong historical value, introduced by the great cleric Syiah Kuala in the 17th century AD. In addition to functioning as entertainment, Seudati is also a medium for preaching that conveys religious messages through Islamic poetry. However, modernization has caused a shift in function from religious rituals to commercial performing arts, which risks reducing its spiritual value. The recommendation of this study is to integrate Seudati into cultural and religious education programs in schools, and to support the regeneration of artists through training and revitalization programs. The implication of this study is the preservation of Seudati as an intangible cultural heritage that not only strengthens Aceh's identity but also becomes a relevant media for preaching in the contemporary context.